Analisis Penerapan Coretax dan Implikasinya pada Tingkat Kepatuhan Wajib Pajak Berbasis Tax Compliance: Slippery Slope Framework - Ariyanto Telaumbanua; I Gusti Ketut Agung Ulupui; Tresno Eka Jaya (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This research investigates individual taxpayers' perceptions regarding the CoreTax system implementation using the Technology Acceptance Model (TAM) approach, while simultaneously analyzing its impact on taxpayer compliance through the Slippery Slope Framework (SSF). Utilizing a qualitative approach with a phenomenological design, data were gathered through observations, semi-structured interviews, and documentation involving a tax extension officer from the Regional Office of the Directorate General of Taxes (DJP) Banten and individual taxpayers experienced in both SIDJP and CoreTax. The findings reveal that CoreTax offers significant benefits, including automated data processing, integrated tax services, and streamlined administrative access within a single platform. Nevertheless, the perceived ease of use remains affected by technical constraints and varying levels of digital literacy among taxpayers. From the SSF perspective, CoreTax bolsters the power dimension through rigorous digital surveillance and nurtures the trust dimension via enhanced transparency and service quality. The synergy between these two dimensions ultimately fosters taxpayer compliance, emerging both voluntarily and through systematic enforcement.